Observation of multilayer Shockley-type stacking fault formation during process of epitaxial growth on highly nitrogen-doped 4H-SiC substrate. (8th January 2019) - Suo, Hiromasa; Yamashita, Tamotsu; Eto, Kazuma; Osawa, Hiroshi; Kato, Tomohisa; Okumura, Hajime
Abstract: We investigated the formation of double Shockley-type stacking fault (DSF) and other types of stacking fault (SF) during a process of epitaxial growth by chemical vapor deposition on a highly nitrogen-doped 4H-SiC substrate. By comparing the bulk substrate before epitaxial growth and the substrate after growth with an epitaxial layer, bar-shaped SFs turned out to have formed during the process of epitaxial growth on the highly nitrogen-doped substrate. These bar-shaped SFs were identified to be DSFs and triple Shockley-type stacking faults by scanning transmission electron microscopy.